Anthropometric and physical fitness indicators in the combine draft between the finalist and the eliminated player in the national basketball association all-star slam dunk contest - Tong, T. H.; Wang, G. W. (PLOS ONE, 2024)
Little is known about the difference of anthropometry and physical fitness between the finalist and eliminated player in the NBA all star slam dunk contest. This study aimed to compare the difference on anthropometric and physical fitness indicator in the combine draft between finalist and eliminated player in the national basketball association all star slam dunk contest. Draft data of 32 basketball players (N = 32, age in draft year: 20.69±2.28 years old, height without shoes: 196.75±8.68 cm, weight: 96.85±10 kg, body fat percentage: 6.07±1.23%) participating in the 2000-2015 draft and 2003-2023 slam dunk contest was selected from national basketball association database. It was classified into finals group (FG) (N = 16) and elimination group (EG) (N = 16). Independent sample t-test with cohen`s d was adopted for evaluating the statistical significance of intergroup difference and its effect size. The result indicates that Finalist group was significant less than elimination group on height without shoes (FG vs EG: 193.43±9.47 cm vs 200.06±6.52 cm, P<0.05), standing reach (FG vs EG: 257.66±12.32 cm vs 268.29±10.03 cm, P<0.05) and weight (FG vs EG: 93.38±7.37 kg vs 100.33±11.25 kg, P<0.05). Conversely, compared to elimination group,finalist group has significant better performance on three quarter court sprint (FG vs EG: 3.15±0.1 s vs 3.26±0.12 s, P<0.05), standing vertical jump (FG vs EG: 84.88±5.13 cm vs 78.83±4.9 cm, P<0.05) and max vertical jump (FG vs EG: 102.39±6.47 cm vs 94.79±8.34 cm, P<0.05). However, effect size analysis indicated that height without shoes,standing reach,weight (cohen`s d = 0.73-0.959, 0.7=cohen`s d<1.3, moderate) from the anthropometric indicator and three quarter court sprint, standing vertical jump, and max vertical jump (cohen`s d = 0.97-1.21, 0.7=cohen`s d<1.3, moderate) from physical fitness indicator has moderate effect size, whereas effect size of body fat percentage, wingspan and lane agility time (cohen`s d = 0.31-0.67, 0.3=cohen`s d<0.7, small) was small. To conclude, specific anthropometric and physical fitness indicator shows clear difference between finals group and elimination group. Height without shoes, standing reach,weight in anthropometry and three quarter court sprint, standing vertical jump, and max vertical jump in physical fitness are key indicator to slam dunk performance. In line with the result in the study, NBA staff can select suitable rookies for slam dunk contest. Similiarly, coach from NBA or other basketball league, who want to improve the player`s slam dunk performance, should use specific training programs to develop the slam dunk-related indicator.